The Role of Marketing Flexibility and Marketing Improvisation in Marketing Crisis Management: An Applied Study at Distribution Body of Oil Products at the Middle Euphrates - Ahmed Kadem Abed AL Aboudy; Karrar Sameer Kareem (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The research aims to clarify the role of marketing flexibility and marketing improvisation in managing marketing crises, through an exploratory study of the opinions of administrative leaders at distribution body of oil products at the Middle Euphrates. The importance of the research stems from the fact that marketing crises pose a direct threat to the continuity of organizations, especially those operating in vital sectors such as the oil products sector, which necessitates adopting effective strategies and mechanisms to deal with these crises. The research relied on the descriptive-analytical method, where a questionnaire was designed and distributed to a sample of administrative leaders, in addition to conducting supporting interviews to reinforce the study’s findings. The data were analyzed using a set of descriptive and inferential statistical methods. The findings revealed a statistically significant positive correlation between marketing flexibility and the marketing crisis management capabilities of the body and the role of marketing improvisation in the initial stage of crisis response, and the role of improvisation in reducing the adverse impact of a crisis, and the barriers to the application of flexibility and improvisation, including bureaucratic constraints and weak administrative qualification. The findings suggest that it is necessary to strengthen the culture of marketing flexibility in policies and plans, to enhance the marketing improvisation skills of leaders, and to activate early warning systems and simplify decision-making mechanisms, in order to build a more effective capacity to cope with future marketing crises.